Analysis of motor cycle helmet under static and dynamic conditions considering different materials. (2021) - Shankar, S.; Nithyaprakash, R.; Praveen, S.; Sathish Kumar, S.; Sriram, A.M.
Abstract: Head injuries are highly impactable for motorized two wheeler users causing injury, disabilities and sometimes leading to death. Helmets are manufactured using different materials especially it depends on applications in which it is utilized. In this work, initially the helmet is modelled with the similar dimensions as per the available manufacturing data. The main objective of this work is to analyse the performance of helmet with five different materials such as ACRYLONITRILE BUTADIENE STYRENE (ABS), POLYCARBONATE (PC), POLYSTYRENE, ABS + PC PLASTIC and Epoxy E-Glass. The modelled helmet is subjected to static and dynamic analyses for choosing the best material by evaluating its mechanical strength such as total deformation, strain energy and equivalent stress using ANSYS. In static analysis, helmet model is subjected with different loads with different conditions to calculate total deformation, strain energy and equivalent energy. While considering dynamic analysis, the helmet model is subjected to loading by covering with two rectangular plates. One side is fixed and other is dropped from a height of 3 m. ABS and Polycarbonate produces more or less same deformation when compared with other materials which results in high strain energy.